Find the general solution to the given partial differential equation and use it to find the solution satisfying the given initial data.
"\\frac{\\partial u}{\\partial x}=-(2x+y)\\frac{\\partial u}{\\partial y}"
"u(0,y)=1+y^2"
"\\frac{dx}{1}=\\frac{dy}{2x+y}"
"(2x+y)dx-dy=0"
"\\mu(x)=e^{-x}"
"e^{-x}y'-e^{-x}y=2xe^{-x}"
"\\frac{d}{dx}(ye^{-x})=2xe^{-x}"
"ye^{-x}=\\int 2xe^{-x}dx=-2e^{-x}(x+1)+c"
"u(x,y)=c"
"ye^{-x}+2e^{-x}(x+1)=c"
"u(x,y)=ye^{-x}+2e^{-x}(x+1)"
"u(0,y)=y+2=y^2+1"
"y^2-y-1=0"
"y_1=\\frac{1-\\sqrt{5}}{2}"
"u_1(x,y)=\\frac{1-\\sqrt{5}}{2}e^{-x}+2e^{-x}(x+1)"
"y_2=\\frac{1+\\sqrt{5}}{2}"
"u_2(x,y)=\\frac{1+\\sqrt{5}}{2}e^{-x}+2e^{-x}(x+1)"
Comments
Leave a comment